JAV lietuvių bibliotekos XIX amžiuje - Raguotis, Bronius (Knygotyra, 1985)
The cultural history of Lithuanian emigrants in the United States interests a great amount of scientists in Lithuania. However, the history of the libraries founded by Lithuanian emigrants was not explored until now. This article is the first attempt to survey the foundation and development of these libraries in the end of XIX-th century (1885–1900).The foundation of the libraries by the Lithuanian emigrants in the United States was very difficult, highly specific and complex. The idea of their organization belonged lo the progressive public men of the Lithuanian emigration (J. Šliūpas, J. Adomaitis-Šernas, J. Paukštis and others).The knowledge about the activities of the above mentioned libraries is scarce and approximate. According to the data gathered by the author 50 libraries were founded and worked during the spoken period. Besides there were collections of Lithuanian books in some public libraries of the United States.The stocks of the emigrant libraries were very poor. They consisted of only some tens of titles. The libraries which existed for a longer lime had more books (e. g. the library of the S. Daukantas Union in Chicago, the Central library of the Lithuanian Association in America).The foundation of such libraries in the USA was followed by the fight between various ideological trends in the Lithuanian emigration. The libraries of the Lithuanian emigrants in the USA which were active in the end of XIXth century created the base for the development of the contemporary Lithuanian library systems in the United States.